Vocational Trainings for Economic and Psychological Empowerment of Farm Women: A Study of Nainital District - Singh, Neha; Bhardwaj, Neelam; Jukaria, Sudha; Kashyap, S.K.; Amardeep, (Indian Journal of Extension Education, 2020)
Various organization and institutes have taken the responsibility to train rural women in different sectors. Krishi Vigyan Kendras are working at grassroot level to empower the women in agriculture and allied fields by imparting training in different subject matter areas. KVK, Jeolikote had played significant role in improving the conditions of hill women and the study conducted in Nainital district falls in its jurisdiction. Data from 90 selected respondents shows significant difference between beneficiaries and non-beneficiaries in the level of economic & psychological empowerment. Three forth of the beneficiaries had high level of empowerment whereas only 15.55 per cent of non-beneficiaries were having high level of empowerment. Majority of beneficiaries had high expenditure level followed by high level of control over the economic resources. Most of the respondents had high level of critical consciousness among beneficiaries group. Whereas majority of beneficiaries had high level of role perception followed by none of the beneficiaries were found to have low level of role perception.
Keywords: Empowerment; Krishi Vigyan Kendra; Training; Women